Effectiveness of forest conservation on private land - Laturi, J.; Lintunen, J.; Pohjola, J.; Rautiainen, A.; Uusivuori, J. (Natural Resources Institute Finland, Luke, 2016)
In forest economics literature leakage effects of forest conservation have been identified both at a global and national scales, when protection of land in one region leads to intensified timber harvests in another region. We analyze the effectiveness of forest conservation at national scale in a case where forest owners derive both monetary and amenity values from forests. A partial equilibrium model FinFEP (Finnish Forest and Energy Policy) is used to form scenarios with and without a government imposed forest land conservation program in Finland. We find that a strong leakage impact exists connected to national land conservation programs. Following simulated conservation programs where 50 000 – 450 000 ha of private land with over 100 year old forests were put under protection, the total area of old-growth forests (> 100 years) increased only between 33 % - 37 % of the initially protected land area. For sensitivity analysis, we varied the coverage of the conservation program, investment and final product demand scenarios. The results indicate that the effectiveness of forest conservation depends on the capacities of forest and energy industries, the size of protected area and the demand of the final goods.
Keywords: conservation; forest and energy industries; leakage; non-industrial private forests; partial equilibrium model; voluntary conservation